Reading strategies used by EFL students for academic texts / Arifah Mardiningrum and Rika Salsabilla - Mardiningrum, Arifah; -, Rika Salsabilla (Universiti Teknologi MARA, 2022)
Reading an academic text might pose a certain challenge for an English as a Foreign Language (EFL) learner with its formal form and specific jargons. Thus, finding the best strategies to face the challenge that work best for the learner is crucial. The current study aimed at finding the most used reading strategies used by 186 university students in an English Education Department of one private university in Indonesia and the different choice made by male and female students. Applying a cross-sectional survey design, the study utilized Survey of Reading Strategies (SORS) questionnaire by Mokhtari and Sheorey (2001) to collect the data. The study found that Problem-Solving Strategies were the most used strategy with the value of M=3.9881. Meanwhile, an independent t-test showed the value of sig 2-tailed of 0.006 < 0.05, which purports that there was a statistically significant difference between male and female students in their choice of reading strategies although the strategies mostly chosen was the same, namely the Problem-Solving Strategies. This gave an implication that problem-solving strategies might be the ones students felt comfortable using and likely to be the ones used and encouraged in the teaching and learning process. The significant difference between the male and female students also implies that the latter have more awareness of using reading strategies that they needed.